Experimental validation of a kilovoltage x‐ray source model for computing imaging dose. Issue 4 (28th March 2014) - Poirier, Yannick; Kouznetsov, Alexei; Koger, Brandon; Tambasco, Mauro
Abstract : Purpose: : To introduce and validate a kilovoltage (kV) x‐ray source model and characterization method to compute absorbed dose accrued from kV x‐rays. Methods: : The authors propose a simplified virtual point source model and characterization method for a kV x‐ray source. The source is modeled by: (1) characterizing the spatial spectral and fluence distributions of the photons at a plane at the isocenter, and (2) creating a virtual point source from which photons are generated to yield the derived spatial spectral and fluence distribution at isocenter of an imaging system. The spatial photon distribution is determined by in‐air relative dose measurements along the transverse (x) and radial (y) directions. The spectrum is characterized using transverse axis half‐value layer measurements and the nominal peak potential (kVp). This source modeling approach is used to characterize a Varian ® on‐board‐imager (OBI ® ) for four default cone‐beam CT beam qualities: beams using a half bowtie filter (HBT) with 110 and 125 kVp, and a full bowtie filter (FBT) with 100 and 125 kVp. The source model and characterization method was validated by comparing dose computed by the authors' inhouse software (kVDoseCalc) to relative dose measurements in a homogeneous and a heterogeneous block phantom comprised of tissue, bone, and lung‐equivalent materials. Results: : The characterized beam qualities and spatial photon distributions are comparable to reported values in the literature. Agreement between computed and measured percent depth‐dose curves is ⩽2% in the homogeneous block phantom and ⩽2.5% in the heterogeneous block phantom. Transverse axis profiles taken at depths of 2 and 6 cm in the homogeneous block phantom show an agreement within 4%. All transverse axis dose profiles in water, in bone, and lung‐equivalent materials for beams using a HBT, have an agreement within 5%. Measured profiles of FBT beams in bone and lung‐equivalent materials were higher than their computed counterparts resulting in an agreement within 2.5%, 5%, and 8% within solid water, bone, and lung, respectively. Conclusions: : The proposed virtual point source model and characterization method can be used to compute absorbed dose in both the homogeneous and heterogeneous block phantoms within of 2%–8% of measured values, depending on the phantom and the beam quality. The authors' results also provide experimental validation for their kV dose computation software, kVDoseCalc.